Unique catalytic activities and scaffolding of p21 activated kinase-1 in cardiovascular signaling - Yunbo eKe; Ming eLei; Xin eWang; R. John Solaro (Frontiers Media S.A., 2013)
P21 activated kinase-1 has diverse functions in mammalian cells. Although a large number of phosphoproteins have been designated as Pak1 substrates from in vitro studies,emerging evidence has indicated that Pak1 may function as a signaling molecule through a unique molecular mechanism-scaffolding. By scaffolding, Pak1 delivers signals through an auto-phosphorylation-induced conformational change without transfer of a phosphate group to its immediate downstream effector(s). Here we review evidence for this regulatory mechanism based on structural and functional studies of Pak1 in different cell types and research models as well as in vitro biochemical assays. We also discuss the implications of Pak1 scaffolding in disease-related signaling processes and the potential in cardiovascular drug development.